An unusual case of acute chest pain - Ananda Datta; Raghavendrun Sivasankar (The Journal of Association of Chest Physicians)
Thoracic musculoskeletal disorders are important differential diagnoses in patients presenting to the emergency department with acute-onset chest pain. Although fractures of the ribs usually occur due to trauma, non-traumatic fractures can be seen in the setting of vigorous as well as repetitive coughing. Usually, ribs with malignant or osteoporotic involvement are susceptible to breaking. Uncommonly, cough-induced fractures have been reported in healthy young individuals. Here, we present a case of a 32-year-old healthy man who suffered a fracture of the left seventh rib following a bout of violent coughing.